Ethical Governance Frameworks for HR AI: Policies, Audits, and Accountability Models - Radha, P; Ealias, Basil; Lamichhane, Basu Dev; Neupane, Dasarath (International Journal of Atharva, 2026)
The adoption of AI in Human Resource (HR) functions - recruitment, performance evaluation, workforce analytics, and employee support—has created a growing need for ethical governance frameworks that ensure these systems are fair, transparent, secure, and accountable. While many organizations publish AI ethics principles, practical gaps remain in translating principles into operational controls, especially in high-stakes employment decisions. This research develops and evaluates an ethical governance framework for HR AI that integrates policies, audits, and accountability models across the AI lifecycle. The study proposes a governance model built around three pillars: (1) Policy architecture, including acceptable-use rules, data minimization and consent standards, role-based access, vendor requirements, and human oversight thresholds for high-impact decisions; (2) Audit mechanisms, including pre-deployment risk assessments, bias and validity testing, documentation practices (e.g., model/data reporting), and continuous monitoring for drift, disparate impact, and unintended consequences; and (3) Accountability structures, defining decision rights, escalation pathways, review boards, incident response, and mechanisms for employee/candidate recourse. Using a mixed-methods design, the research first gathers stakeholder requirements through interviews with HR leaders, legal/compliance staff, data scientists, and employees. It then operationalizes the framework into a practical toolkit (checklists, RACI matrix, audit templates, and KPI dashboards) and evaluates it via case-based simulations or pilot implementations in HR AI use cases. Expected contributions include (a) a validated set of governance controls tailored to HR-specific risks such as discrimination, surveillance, and privacy breaches, (b) measurable governance KPIs for responsible HR AI, and (c) actionable guidance for aligning HR AI practices with legal compliance and organizational trust.